L'adaption de l'amengement forestier a des situations diverses - Bertrand, A.; Babin, D.; Nasi, Robert (1999)
Examples are used to illustrate the different present-day forms of forest management, based first and foremost on decision-making procedures governing management choices rather than on technical criteria governing the choice and implementation of programmes. These examples range from the Gabonese forest to Madagascar to the arid regions of the Sahel in Mali and Niger. They also involve different spatial scales ranging from the village forest to large forested areas, and then to the nationwide dimension. Last of all, they incorporate various targets - timber production, raffia exports, biodiversity conservation - and take many different objectives into account (livestock raising, honey, etc.)